PROBOSIS LATERALIS - Ayub, Muhammad Waqas; Waleem, Saadat; Feroz, Faheem; Waqas, Asma (Pakistan Armed Forces Medical Journal, 2021)
Proboscis lateralis is an embryological inconsistency which is identified with the middle facial cleft. This outcomes in fragmented arrangement of one side of nose. This underdeveloped nose structure is situated close to the nose but off the midline. It seems like a cylinder and is appended at the undeveloped combination line anytime between the foremost maxillary interaction and the frontonasal cycle. This issue ought to be tended to at an early age and with stage shrewd methodology as this proboscis itself is a valuable design for remaking. We report an instance of proboscis lateralis in a 1-year-old female patient.